Ferroelectric-gated variable-area capacitors with large capacitance tuning ratio using Ce-doped HfO2 film for both gate insulator and capacitor layer. (9th March 2023) - Miyasako, Takaaki; Yoneda, Shingo; Hosokura, Tadasu; Kimura, Masahiko; Tokumitsu, Eisuke
Abstract: We demonstrate a three-terminal variable-area capacitor integrated with a ferroelectric-gate field-effect transistor (FeFET) and a ferroelectric capacitor. A FeFET using an indium tin oxide (ITO) channel and a ferroelectric Hf0.86 Ce0.14 O2 gate insulator was fabricated by chemical solution deposition. The fabricated FeFET exhibited a high on-current of ∼0.18 mA μ m −1 and a large on-/off-current ratio of 10 6 . The large charge controllability of the FeFET allows the conductive ITO channel to act as an electrode switch that connects and disconnects two capacitors. In order to increase the capacitance density and the capacitance tuning ratio (CTR), we propose a structure wherein a 25-nm-thick ferroelectric film is applied as both a gate insulator and a capacitor. The proposed structure exhibited a large capacitance density of 12.5 nF mm −2 and a wide CTR of approximately 10 000. This work facilitates future integration of passive and active components for advanced highly efficient and miniaturized electronics.